Calculus early transcendentals - Briggs, William L.; Cochran, Lyle; Gillett, Bernard (Pearson Education Limited, 2015)
In writing this text, we identified content in the calculus curriculum that consistently presents challenges to our students. We made organizational changes to the standard presentation of these topics or slowed the pace of the narrative to facilitate students' comprehension of material that is traditionally difficult. Two noteworthy modifications to the traditional table of contents for this course appear in the material for Calculus II and Calculus III. Often appearing near the end of the term, the topics of sequences and series are the most challenging in Calculus II. By splitting this material into two chapters, we have given these topics a more deliberate pace and made them more accessible without adding significantly to the length of the narrative.